The hypothetical protein P47 of Clostridium botulinum E1 strain Beluga has a structural topology similar to bactericidal/permeability-increasing protein. - Lam, Kwok-Ho; Qi, Ruifeng; Liu, Shun; Kroh, Amelie; Yao, Guorui; Perry, Kay; Rummel, Andreas; Jin, Rongsheng (eScholarship, University of California, 2018)
Botulinum neurotoxins (BoNTs) are causative agents of the life-threatening disease botulism. They are naturally produced by species of the bacteria Clostridium botulinum as stable and non-covalent complexes, in which the BoNT molecule is assembled with several auxiliary non-toxic proteins. Some BoNT serotypes, represented by the well-studied BoNT serotype A (BoNT/A), are produced by Clostridium strains that carry the ha gene cluster, which encodes four neurotoxin-associated proteins (NTNHA, HA17, HA33, and HA70) that play an important role to deliver and protect BoNTs in the gastrointestinal tract during oral intoxication. In contrast, BoNT/E- and BoNT/F-producing strains carry a distinct gene cluster that encodes five proteins (NTNHA, P47, OrfX1, OrfX2, and OrfX3, termed the orfX cluster). The structures and functions of these proteins remain largely unknown. Here, we report the crystal structure of P47 resolved at 2.8Å resolution. Surprisingly, P47 displays a structural topology that is similar to bactericidal/permeability-increasing (BPI) like proteins, which were previously identified only in eukaryotes. The similarity of a hydrophobic cleft of P47 with the phospholipid-binding groove of BPI suggests that P47 might be involved in lipid association to exert its function. Consistently, P47 associates and induces aggregation of asolectin-containing liposomes in a protein- and lipid-concentration dependent manner. These findings laid the foundation for future structural and functional studies of the potential roles of P47 and OrfX proteins in facilitating oral intoxication of BoNTs.